Comparison of the graph-theoretical force method and displacement method for optimal design of frame structures. (September 2022) - Kaveh, Ali; Zaerreza, Ataollah
Abstract: In this paper, a graph-theoretical force method is utilized for the analysis of the frame structures to decrease the time required for optimization. The performance and speed of the graph-theoretical force method are compared to those of the displacement method in the optimal design of frame structures. The results indicate that the force method in the considered problems requires less computational time than the displacement method, while both methods have the same accuracy. Additionally, the standard particle swarm optimization algorithm (PSO) is improved to enhance its performance for the optimal design of the steel frames. Benchmark frame examples are studied, and the performance of the graph-theoretical force method and displacement method are compared. The results show that the improved version of the PSO is more robust than the PSO in the optimal design of the steel frames utilizing both methods of analysis.